2004
DOI: 10.1074/jbc.m312039200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-sensing Receptor-mediated ERK1/2 Activation Requires Gαi2 Coupling and Dynamin-independent Receptor Internalization

Abstract: The calcium-sensing receptor (CaR) recently has been shown to activate MAP kinase (ERK1/2) in various cell types as well as in heterologous expression systems. In this study we show that the CaR agonist NPS R-467 (1 M), which does not activate the CaR by itself, robustly activates ERK1/2 in the presence of a low concentration of Ca 2؉ (0.5 mM CaCl 2 ) in human embryonic kidney (HEK) cells permanently expressing the human CaR (HEK-hCaR). Ca 2؉ (4 mM) also activates ERK1/2 but with differing kinetics. CaR-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 50 publications
5
31
0
Order By: Relevance
“…In detail, it has been reported that the activation of CASR by its agonists or the calcimimetic NPS R568, which binds to the transmembrane domains (TMDs) of the receptor and activates it through an allosteric mechanism, stimulates the proliferation of several cell types, action that likely involves CASR-mediated activation of MAPK, as observed in rat fibroblasts and ovarian surface cells (McNeil et al 1998b; review by and Hobson et al (2003)). Indeed, in bovine parathyroid and in CASR-transfected HEK cells, elevating Ca 2C or adding NPS R-467 elicited rapid, dosedependent phosphorylation of MAPK3 and 1 (Kifor et al 2001, Holstein et al 2004. Our data showed Functional role of CASR in mammalian oocytes that incubation with NPS R-467 resulted in an increase in MAPK 3/1 activity at 15 min which still remained high at 26 h culture time compared with controls.…”
Section: Discussionsupporting
confidence: 47%
“…In detail, it has been reported that the activation of CASR by its agonists or the calcimimetic NPS R568, which binds to the transmembrane domains (TMDs) of the receptor and activates it through an allosteric mechanism, stimulates the proliferation of several cell types, action that likely involves CASR-mediated activation of MAPK, as observed in rat fibroblasts and ovarian surface cells (McNeil et al 1998b; review by and Hobson et al (2003)). Indeed, in bovine parathyroid and in CASR-transfected HEK cells, elevating Ca 2C or adding NPS R-467 elicited rapid, dosedependent phosphorylation of MAPK3 and 1 (Kifor et al 2001, Holstein et al 2004. Our data showed Functional role of CASR in mammalian oocytes that incubation with NPS R-467 resulted in an increase in MAPK 3/1 activity at 15 min which still remained high at 26 h culture time compared with controls.…”
Section: Discussionsupporting
confidence: 47%
“…The efficient activation of the 990G CASR in terms of p44/42 ERK phosphorylation has been observed even at lower R-568 concentrations. The binding site for R-568 has been identified within the transmembrane domain of human CASR (Holstein et al 2004). R-568 has been demonstrated to stabilize WT and mutant CASR favoring the active receptor conformations (Miedlich et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Mitogen-activated protein kinase (MAPK) activity plays an important role in heart hypertrophy. 28 Holstein 29 showed that activation of the CaSR activates ERK-1/2 kinases. The ERK-1/2 signaling was shown to promote adaptive hypertrophy with normalized wall stress and compensation for increased load.…”
Section: Discussionmentioning
confidence: 99%